Association of International Marathons and Road Races
Official web site of the Association of International Marathons and Road Races (AIMS). Content: Information on the Association of International Marathons and Road Races (AIMS), News, Race Calendar , Race Directory , Race Directors , IMMDA , Statistics , Membership Info , Links .